Overexpression of Large‐Conductance Calcium‐Activated Potassium Channels in Human Glioblastoma Stem‐Like Cells and Their Role in Cell Migration. Issue 9 (10th April 2017) - Rosa, Paolo; Sforna, Luigi; Carlomagno, Silvia; Mangino, Giorgio; Miscusi, Massimo; Pessia, Mauro; Franciolini, Fabio; Calogero, Antonella; Catacuzzeno, Luigi
Abstract : Glioblastomas (GBMs) are brain tumors characterized by diffuse invasion of cancer cells into the healthy brain parenchyma, and establishment of secondary foci. GBM cells abundantly express large‐conductance, calcium‐activated potassium (BK) channels that are thought to promote cell invasion. Recent evidence suggests that the GBM high invasive potential mainly originates from a pool of stem‐like cells, but the expression and function of BK channels in this cell subpopulation have not been studied. We investigated the expression of BK channels in GBM stem‐like cells using electrophysiological and immunochemical techniques, and assessed their involvement in the migratory process of this important cell subpopulation. In U87‐MG cells, BK channel expression and function were markedly upregulated by growth conditions that enriched the culture in GBM stem‐like cells (U87‐NS). Cytofluorimetric analysis further confirmed the appearance of a cell subpopulation that co‐expressed high levels of BK channels and CD133, as well as other stem cell markers. A similar association was also found in cells derived from freshly resected GBM biopsies. Finally, transwell migration tests showed that U87‐NS cells migration was much more sensitive to BK channel block than U87‐MG cells. Our data show that BK channels are highly expressed in GBM stem‐like cells, and participate to their high migratory activity. J. Cell. Physiol. 232: 2478–2488, 2017. © 2016 Wiley Periodicals, Inc. Abstract : We investigated the expression of BK channels in GBM stem‐like cells using electrophysiological and immunochemical techniques, and assessed their involvement in the migratory process of this important cell subpopulation. In U87‐MG cells, BK channel expression and function were markedly upregulated in GBM stem‐like cells expressing CD133, as well as other stem cell markers. In addition, transwell migration tests showed that GBM stem‐like cell migration was very sensitive to BK channel block.